Framing of a successful female athlete in a Malaysian English language daily : a multimodal analysis / Noor Dalina Khalid - Noor Dalina, Khalid (2012)
This study aims at examining how the Malaysian World No.1 female squash player, Nicol Ann David is being framed in one of the English-language Malaysian dailies, The Star. Studies on stylistics features of news reporting have frequently focused on male athletes (Klien, 1988) and as such, this study would further enrich the field of sports news reporting by focusing on reports of a female athlete. The added focus on analysing the visuals that accompany the reports would also justify the need for this study as previous studies on sports news are mostly linguistically based. Nicol Ann David was made the subject of the study as she is the most outstanding female athlete in Malaysia. Named the eight-time National Sportswoman of the year and the five-time world champion in 2010, Nicol is also ranked World No. 1 for 56 consecutive months while reports on Nicol were collected from The Star as it is the most circulated and the most widely read English-language daily in Malaysia (Audit Bureau of Circulation 2010). The analysis will focus on the lexical and visual resources of the reports, with visuals claimed to be the element to enhance the credibility of a text (Shirato & Yell, 2000). These linguistic and non-linguistic features of a text are fundamental to ensure the message intended is comprehended. The framework for linguistic analysis is based on Framing Theory by Goffman (1974) and specifically Kian’s (2006) framework of framing athletes is adopted in analysing the lexical items in the reports. Results of the analysis showed that three major frames emerged; personalization frame, achievement frame and strength frame where personalization is the new frame introduced by this study. Another new frame established by this study is the localisation frame, though it is merely a minor frame. The visuals that accompany the reports were analysed using the Interaction Analysis of Kress and Van Leeuwen (1996, 2006) where the contact and social distance between images of Nicol and the readers of the reports were examined. This is to observe whether these visuals reflected the frames that emerged in the linguistic analysis. Results revealed that the images provide information on Nicol’s achievements and display her strength /athletic prowess. In addition, Nicol was being portrayed as having close relationship visually with her audience just as being drawn by the lexical findings. Hence, the study shows that the frames realized by the lexical items used are also realized in the visuals provided. This study is hoped to provide a rare insight on coverage of a woman athlete in the printed media and sport reporting in Malaysia and across the field. Besides enlightening the society that marginalization and trivialization of women athletes in sport and the media is not a global ideology, this study would initiate more studies on women athletes from various perspectives.